Millennial Makeover MySpace, YouTube, and the Future of American Politics - Winograd, Morley; Hais, Michael D. (Rutgers University Press, 2008)
It happens in America every four decades and it is about to happen again. America’s demand for change in the 2008 election will cause another of our country’s periodic political makeovers. This realignment, like all others before it, will result from the coming of age of a new generation of young Americans—the Millennial Generation—and the full emergence of the Internet-based communications technology that this generation uses so well. Beginning in 2008, almost everything about American politics and government will transform—voting patterns, the fortunes of the two political parties, the issues that engage the nation, and our government and its public policy. Building on the seminal work of previous generational theorists,Morley Winograd and Michael D. Hais demonstrate and describe, for the first time, the two types of realignments—"idealist" and "civic"—that have alternated with one another throughout the nation’s history.